Crystal chemistry of mimetite, Pb10(AsO4)6Cl1.48O0.26, and finnemanite, Pb10(AsO3)6Cl2 - Baikie, Tom (2014)
The crystal chemistries of synthetic mimetite, Pb10(As5+O4)6(Cl2-xOx/2), a neutral apatite, and finnemanite, Pb10(As3+O3)6Cl2, a reduced apatite, were characterized using a combination of X-ray powder diffraction, neutron diffraction, transmission electron microscopy and X-ray photoelectron spectroscopy. Both phases conform to hexagonal P63/m symmetry; however, the temperature-driven transformation of clinomimetite to mimetite described earlier was not confirmed. The average mimetite structure is best described through the introduction of partially occupied oxygen sites. A better understanding of the mixed arsenic speciation in apatites can guide the formulation of waste form ceramics and improve models of long-term durability after landfill disposal.